ChemInform Abstract: Nickel‐Catalyzed α‐Arylation of Ketones with Phenol Derivatives. Issue 1 (January 2015) - Takise, Ryosuke; Muto, Kei; Yamaguchi, Junichiro; Itami, Kenichiro
Abstract The nickel‐catalyzed α‐arylation of ketones with readily available phenol derivatives (esters and carbamates) provides access to useful α‐arylketones.